Natural products: Their chemistry and biological significance (Longman, 1994)
The book provides a fascinating account of the structure, chemistry, biosynthesis and biological activity of most types of natural organic compounds. Each chapter is deveoted to particular class of compounds. Some, like carbohydrates, nucleosides/nucleotides and amino acids/peptides, are products of primary metabolism and are vital for the maintenance of life processes. Others, like terpenoids/steroids, phenolics, fatty acid metabolites and alkaloids, are products of secondary metabolism and have toxicological, pharmacological and ecological importance. Interesting and intriguing chemistry is involced in their in vivo production and in their laboratory use, and their role as structural materails and biologically active molecules (toxins, hormones, drugs, etc.) is of unparalleled importance. all of these aspects are covered comprehensively within this book